Efektivitas Pengelolaan Penerimaan Negara Bukan Pajak (PNBP) pada Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL) Bandung - Aulia Putri Azahra; Nenden Kostini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The effectiveness of Non-Tax State Revenue (PNBP) management plays a crucial role in strengthening state revenue and promoting the optimization of public financial governance. This research is motivated by the fluctuating trend in PNBP realization at the Office of State Assets and Auction Services (KPKNL) Bandung over the past five years, which indicates a lack of consistency in achieving revenue targets. The purpose of this study is to evaluate the effectiveness of PNBP management at KPKNL Bandung from 2019 to 2023. The research employs a quantitative method with a descriptive analysis technique using effectiveness ratio calculations. The data used include secondary data in the form of Financial Statements and Notes to Financial Statements for the 2019–2023 period, as well as primary data obtained through interviews and direct observation. The analysis results show that the effectiveness of PNBP management has fluctuated, with the years 2019 and 2023 classified as effective, achieving 110.99% and 103.14% respectively. In contrast, 2020 and 2022 fell into the less effective category with achievements of 74.86% and 79.81%, while 2021 was considered ineffective with a score of 56.00%. The five-year average effectiveness was 84.96%, which is still categorized as less effective. In conclusion, the effectiveness of PNBP management at KPKNL Bandung needs to be improved through the optimization of service volume, successful auction performance, and strategies for handling state receivables.